Isobaric sampling apparatus and key techniques for deep sea macro-organisms: A brief review - Wang, Hao; Chen, Jiawang; Zhou, Qixiao; Hu, Xiaohui; Gao, Qiaoling; Guo, Jin; Wang, Ying; Li, Haonan (Frontiers in Marine Science, 2022)
The study of deep-sea fauna is one of the essential themes of marine scientific research. For all that, the biology of deep animals remains largely unknown, such as their behaviors, metabolic characteristics, and mechanisms of adaptation to the deep-sea environment. Obtaining samples in good condition is an essential prerequisite for these investigations. The isobaric samplers were created to keep the organisms as much as possible in the in-situ environment during recovery. This report reviews the history and the application of isobaric samplers for deep-sea animals established by researchers worldwide over the past hundred years. Also, the crucial technologies of isobaric samplers are analyzed and summarized, including pressure compensation, insulation, sealing, etc. Finally, prospects for the future development of isobaric sampling technologies from the aspects of high fidelity, function integration, and real-time communication and integration operation. This review can provide a reference for future design and optimization of fidelity samplers for deep-sea animals.